The occurrence of early complications after subarachnoid analgesia in patients undergoing elective - Grabowska- Gaweł, Anna; Ulenberg, Grzegorz; Ulenberg, Agata (Journal of Education, Health and Sport, 2018)
Introduction: Spinal anesthesia, and any method of anesthesia, is not free of complications and side effects. Despite the fact that the use of thin pencil points, piercing a hard tire can be a headache, sometimes with a large therapeutic problem that is rarely present. Methods: The study was performed in 130 patients aged 28-84 years (mean 56.2 ± 16.2) undergoing orthopedic, urological and surgical operations. Data were obtained from the questionnaire, anesthesia card and nursing documentation and included: sex, age, medication, type and duration of the procedure, presence of degeneration of the spine, obesity, number of intervertebral fractures and complications related to anesthesia. The t-test, the two-fraction test, the Pearson chi-square independence test. Results: Early complications occurred in 43.07% of patients, with no demonstrated their relationship to the type and duration of surgery. A significant association between the age of patients and the incidence of hypotension (p <0.02), a TNS (p <0.55), and nausea and vomiting (p <0.02). These complications were significantly more (p <0.02) in patients under 40 years of age Bradycardia was observed only in 7 patients. Urinary retention requiring bladder catheterization occurred in 5.38% of patients as well as nausea and vomiting, which were accompanied by hypotension and bradycardia. Conclusions: There was no correlation between the occurrence of early complications and the type and duration of surgery. A reduction in the value of SAP and bradycardia was observed in a small percentage of patients. Nausea and vomiting related mainly to young women and accompanied by hypotension and bradycardia.